PENINGKATAN KEMAMPUAN MENYIMAK MELALUI MEDIA WAYANG DOLANAN (Peneliatian Tindakan pada Anak Kelompok B di PAUD Cifor Ceria Kota Depok) - Yulianty, Puji (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2021)
ABSTRACTThis study aims to describe the process and learning outcomes through media wayang dolanan  in improving listening ability. This research was conducted at PAUD Cifor Ceria, Depok City in April 2018. The subjects of the study were B group of 15 students. This research uses action research method. The research procedure consists of: planning, action and observation, reflection. Conducted for 20 meetings divided into two cycles. Data collection techniques are conducted through tests, observations, interviews and documentation studies. Data analysis technique used in this research is qualitative and quantitative data analysis. Pre-action was performed to determine the percentage of listening ability of 54, 7 %, increased to 64,3% after the first cycle, and increased to 81,3% after the second cycle. Listening ability can be developed through telling story with media wayang dolanan, where through media wayang dolanan can be more concentration / focus listening stories, train self-confidence as children try to practice making their own stories, train the patience of children and children will get new information or knowledge.Keywords : listening ability, media wayang dolanan, Early Childhood